A HISTORICAL NARRATIVE AND CRITICAL ANALYSIS OF THE ROOTS AND CAUSES OF CONFLICT IN THE SOUTHERN PHILIPPINES - Jerson Benia Narciso (Universitas Gadjah Mada, 2012)
This paper highlights a chronology of signicant historical events since pre-colonial times up to the present that have signicantly contributed to the conict in Southern Philippines. It also describes and analyzes the roots and causes of the conict and how these are being addressed at the moment both by the Philippine government and the different Islamic liberationist groups who are the main actors and players in the conict.This paper employs both historical and structural analysis to obtain a much broader and complete picture of the historical as well as socio-political, cultural, and economic realities reigning in the Southern Philippines. The study shows that the problem of conict in Mindanao is quite complex and complicated. Thus, it requires a much broader and careful understanding and analysis of the problem, as well as solutions that can be agreed upon by contending groups and factions toward a peaceful and negotiated approach to the Mindanao peace process.